Collaboration of Stakeholders In Formation and Development Nagari-Owned Enterprise - Rozidateno Putri Hanida; Bimbi Irawan; Syamsurizaldi Syamsurizaldi; Wewen Kusumi Rahayu (Indonesian Association for Public Administration, 2017)
Communal land is one of the village assets that can be utilized for the benefit of the public, and it can be managed by an enterprise owned by the village, devoted to creating self-reliance of the village. Law No. 6 of 2014 on the village, mandated the management of the village assets in the form of Village-Owned Enterprise (BUMDes), in West Sumatra, it is called Nagari-Owned Enterprise (BUMNag). Nagari Lubuk Malako has several business fields managed in the form of village cooperative, which later transformed into BUMNag. This paper is the result of a research aimed at describing and analyzing how the collaboration was undertaken by many stakeholders in Nagari, in the formation and development of the BUMNag. With the descriptive qualitative method, through analysis of the data in the form of etic and emic, Nagari Government of Lubuk Malako succeeded in changing the form of the management of the business field of smallholding plantation, to be managed by BUMNag. Changes in the form of management are the result of governance collaboration in Nagari. Stakeholders in Nagari, namely indigenous community, private firms, and youth leaders, worked together to increase participation in doing the vertical and horizontal collaboration, and made networking to push Wali Nagari (Head of Nagari) as the governmental component in order to facilitate the formation and development of BUMNag.